Child temperamental reactivity and self-regulation effects on attentional biases - Susa, Georgiana; Benga, Oana; Pitica, Irina; Miclea, Mircea (Frontiers in Psychology, 2014)
This study examined the effects of individual differences in temperamental reactivity (fear) and self-regulation (attentional control) on attentional biases toward threat in a sample of school-aged children. Attentional biases were assessed with pictorial Dot-probe task, comparing attention allocation toward angry (threat-related) vs. neutral and happy faces. Children also completed self-report temperamental measures of fear and attentional control. We compared attentional bias scores in 4 groups of children: high/low fear and high/low attentional control. Results indicated that, in the case of children with high fear and low attentional control, attention was significantly biased toward angry faces compared with children who had low fear and low attentional control. Findings are discussed in terms of the moderating role of individual differences in attentional control in the context of threat, anxiety-related attentional biases in children.